2015
DOI: 10.1007/s00484-015-1014-x
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration of urban trees and its cooling effect in a high latitude city

Abstract: An important ecosystem service provided by urban trees is the cooling effect caused by their transpiration. The aim of this study was to quantify the magnitude of daytime and night-time transpiration of common urban tree species in a high latitude city (Gothenburg, Sweden), to analyse the influence of weather conditions and surface permeability on the tree transpiration, and to find out whether tree transpiration contributed to daytime or nocturnal cooling. Stomatal conductance and leaf transpiration at day an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 163 publications
(85 citation statements)
references
References 39 publications
(49 reference statements)
4
77
0
4
Order By: Relevance
“…2 Map showing the site and trees selected for the study Our findings of positive effects of surface permeability on stem growth and current-year shoot growth (Fig. 3) are in agreement with earlier reports of positive influences of surface permeability on tree vitality, growth and transpiration (Celestian and Martin 2005;Ferrini and Baietto 2007;Grabosky and Gilman 2004;Iakovoglou et al 2001;Jim 1997;Konarska et al 2015;Quigley 2004;Roberts 1977;Sanders et al 2013;Schröder 2008). This effect was probably in part due to the combined effects of better soil aeration (Wiseman 2004), higher soil microbial activity and nutrient release (Gemtos and Lellis 1997), and a cooler and moister belowground and aerial environment immediately surrounding the trees (Celestian and Martin 2004;Graves 1994;Montague and Kjelgren 2004;Mueller and Day 2005).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…2 Map showing the site and trees selected for the study Our findings of positive effects of surface permeability on stem growth and current-year shoot growth (Fig. 3) are in agreement with earlier reports of positive influences of surface permeability on tree vitality, growth and transpiration (Celestian and Martin 2005;Ferrini and Baietto 2007;Grabosky and Gilman 2004;Iakovoglou et al 2001;Jim 1997;Konarska et al 2015;Quigley 2004;Roberts 1977;Sanders et al 2013;Schröder 2008). This effect was probably in part due to the combined effects of better soil aeration (Wiseman 2004), higher soil microbial activity and nutrient release (Gemtos and Lellis 1997), and a cooler and moister belowground and aerial environment immediately surrounding the trees (Celestian and Martin 2004;Graves 1994;Montague and Kjelgren 2004;Mueller and Day 2005).…”
Section: Discussionsupporting
confidence: 87%
“…While a large study with 600 trees in New Jersey, USA, failed to detect any significant relationship between the permeable surface cover and tree growth across nine tree species (Vrecenak et al 1989), other investigations reported enhanced growth and gas exchange of trees surrounded by grass or bare soil compared to those planted over paved surfaces (Celestian and Martin 2005;Ferrini and Baietto 2007;Grabosky and Gilman 2004;Konarska et al 2015;Sanders et al 2013). Clearly, further studies are needed to investigate the links between ground surface permeability and tree functioning, and whether such possible effects are gradual or limited to the most severe cases of impermeability only.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar diurnal pattern of the park cooling effect was found in Gaborone, Botswana (Jonsson, ) and Nagoya, Japan (Hamada and Ohta, ). While the addition of soil moisture can result in higher night‐time air temperature in a park than in a built‐up area (Spronken‐Smith and Oke, ), available soil moisture can also increase cooling due to evaporation and enhanced tree transpiration (Whitlow and Bassuk, ; Kjelgren and Clark, ; Rahman et al , ; Konarska et al , ). In hot, dry climates, urban parks can be up to 7 °C cooler than their surroundings in the evening, while during daytime they can be even warmer unless they are irrigated (Spronken‐Smith and Oke, ; Potchter et al , ; Lindén, ).…”
Section: Introductionmentioning
confidence: 99%